Transgenerational Developmental Effects of Immune Priming in the Red Flour Beetle Tribolium castaneum - Schulz, Nora K.E.; Sell, Marie Pauline; Ferro, Kevin; Kleinhölting, Nico; Kurtz, Joachim (Frontiers in Physiology, 2019)
Immune priming, the increased chance to survive a secondary encounter with a pathogen, has been described for many invertebrate species, which lack the classical adaptive immune system of vertebrates. Priming can be specific even for closely related bacterial strains, last up to the entire lifespan of an individual, and in some species, it can also be transferred to the offspring and is then called transgenerational immune priming (TGIP). In the red flour beetle Tribolium castaneum, a pest of stored grains, TGIP has even been shown to be transferred paternally after injection of adult beetles with heat-killed Bacillus thuringiensis. Here we studied whether TGIP in T. castaneum is also transferred to the second filial generation, whether it can also occur after oral and injection priming of larvae and whether it has effects on offspring development. We found that paternal priming with B. thuringiensis does not only protect the first but also the second offspring generation. Also, fitness costs of the immune priming became apparent, when the first filial generation produced fewer offspring. Furthermore, we used two different routes of exposure to prime larvae, either by injecting them with heat-killed bacteria or orally feeding them B. thuringiensis spore culture supernatant. Neither of the parental larval priming methods led to any direct benefits regarding offspring resistance. However, the injections slowed down development of the injected individuals, while oral priming with both a pathogenic and a non-pathogenic strain of B. thuringiensis delayed offspring development. The long-lasting transgenerational nature of immune priming and its impact on offspring development indicate that potentially underlying epigenetic modifications might be stable over several generations. Therefore, this form of phenotypic plasticity might impact pest control and should be considered when using products of bacterial origin against insects.